Association of coronary artery calcification with clinical and physiological characteristics in patients with COPD: Results from COSYCONET. (November 2022) - Kahnert, Kathrin; Jörres, Rudolf A.; Jobst, Bertram; Wielpütz, Mark O.; Seefelder, Axinja; Hackl, Caroline M.; Trudzinski, Franziska C.; Watz, Henrik; Bals, Robert; Behr, Jürgen; Rabe, Klaus F.; Vogelmeier, Claus F.; et al.
Abstract: Chronic obstructive pulmonary disease (COPD) is frequently associated with coronary artery disease (CAD). When considering computed tomography (CT) for COPD phenotyping, coronary vessel wall calcification would be a potential marker of cardiac disease. However, non-ECG gated scans as used in COPD monitoring do not comply with established quantitative approaches using ECG-triggered CT and the Agatston score. We studied the diagnostic potential of Agatston scores from non-triggered scans for cardiac disease. The study population was a sub-group of the COPD cohort COSYCONET that underwent CT scanning in addition to comprehensive clinical assessments, echocardiographic data and physician-based diagnoses of comorbidities. Agatston scores from non-contrast enhanced, non-triggered CT were used to identify a cut-off value for CAD via ROC analysis. 399 patients were included (152 female, mean age 66.0 ± 8.2 y). In terms of CAD, an Agatston score ≥1500 AU performed best (AUC 0.765; 95% CI: 0.700, 0.831) and was superior to the conventional cut-off value (400 AU). Using this value for defining groups, there were differences (p < 0.05) in lung function, left atrial diameter and left ventricular end-systolic diameter as well as CT-determined central airway wall thickness pointing towards a bronchitis phenotype. In multivariate analysis, BMI, hyperlipidemia, arterial hypertension, GOLD D (p < 0.05) but particularly Agatston score ≥1500 AU (Odds ratio 10.5; 95% CI: 4.8; 22.6)) were predictors of CAD. We conclude that in COPD patients, Agatston scores derived from non-ECG gated CT showed a much higher cut-off value (1500 AU) for actionable coronary artery disease than the score derived from ECG-triggered CT in cardiology patients. Highlights: CT thorax examinations are frequently used for phenotyping of COPD. Coronary vessel wall calcification can be quantified from non-ECG gated CT scans. The Agatston score can automatically be derived from non-ECG gated CT scans. A higher Agatston-score cut-off value of 1500 AU should be used in this setting.